Resection of a Posterior Mediastinal Mass in a 4-Year-Old Child Complicated by Difficult Airway Management and Emergent Use of Extracorporeal Membrane Oxygenation. (December 2020) - Au, Valerie; Marsh, Benjamin; Benkwitz, Claudia
Literature on posterior mediastinal masses is limited. Furthermore, they have traditionally been described to pose lower cardiopulmonary risks compared with anterior mediastinal masses. Studies on posterior mediastinal masses are even more limited in the pediatric population. We present a case of a large posterior mediastinal mass in a 4-year-old child who presented with extremely difficult airway management during endobronchial intubation due to severe external compression that led to use of an adapted airway management technique with a rigid airway exchanger for lung isolation. Due to the pathology of the mass, a tracheal tear was encountered during surgical dissection and the patient required emergent venovenous extracorporeal membrane oxygenation to allow for successful airway repair and complete resection of the mass.